Turning technological relatedness into industrial strategy: The productivity effects of smart specialisation in Europe - Giacomo Lo Conte; Andrea Mina; Silvia Rocchetta (University College Dublin, UCD School of Economics, 2023)
In this paper we explore the impact of place-based innovation policy in Europe. We focus on the effects of Smart Specialisation strategies on the labour productivity of regional economies. We design an analytical framework that takes into account the entrepreneurial discovery process through which the policy is implemented, and connect the technological relatedness of regions with their specialisation choices. We use an IV estimation approach capable of handling endogeneity problems, and apply it to an extensive dataset of 102 NUTS2 regions extracted from the European Commission Smart Specialisation Portal. The results show that Smart Specialisation strategies increase labour productivity as long as the priorities are set in sectors related to pre-existing technological capabilities, indicating the fundamental importance of path-dependency in diversification choices. The findings deepen our understanding of regional development and innovation strategies, and have relevant implications for the implementation of appropriate policy instruments.
Keywords: O33; R11; 330; Related diversification; Specialization; Regional policy; Innovationpolicy; Place-based Policies